Le atmosfere di Lucia Romualdi (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Lucia Romualdi is an artist active since the 70s in the context of conceptual art. Since 1989 she has been working to a close dialogue with musical languages. Her oeuvreis basically focuses on the relationship between space, music and light, and so she creates performances made of optical equipments which turn on and off according to musical rhythms, that are taken not only from original sound scores, but also from old movies soundtracks and thatare mostly structured on the reading of mathematical rules of solids and voids which do inspire her extremely unusual selected locations. Golden measures, music and sea are her main topics. The sea, in particular, is the element that merges Lucia Romualdi’s artistic journeys, always symbolically marked by the numbers of harbour tides, or through the projection of minimal digital images from old movies and/or showing sea animals taken from ancient manuscripts and printed books. The real structure of the places changes, and it is perceived in a total, complete emotional immersion, measured by mathematical and musical scores, too. You just have to be dazzled by such very personal atmospheres whether in Malibu, Chicago, Antwerp, Prato, Naples, Rome or Samorin. The artist let the visitor be an active protagonist of the visual experience, and he himself is required to establish a connection, apparently indefinite, which becomes certain in that time. The performance concretely experienced by the visitor, by his own hearing and viewing, with his total physical immersion in a not tangible but special space, transcends the architectural context; and only in this way it provides him a contact, a fusion of physical awareness and sentimental emotion, which throws the visitor in a field that is ‘other’, and therefore different.